2017
DOI: 10.1007/s10826-017-0954-7
|View full text |Cite
|
Sign up to set email alerts
|

State Trust in Middle Childhood: An Experimental Manipulation of Maternal Support

Abstract: Attachment representations have traditionally been considered a stable trait, although evidence is found that attachment varies over time and situations conditional upon exposure to life-events and diverse contextual factors. This suggests that attachment consists of both trait and state like components. The current study aimed to evaluate if experiences with maternal support modulate children's state trust in mother's availability. For this purpose, we set up an experimental procedure. First, children watched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 49 publications
3
18
1
Order By: Relevance
“…The current studies’ findings in favor of state attachment variability add to previous studies that found evidence for state attachment fluctuations (e.g., Bosmans, Van de Walle et al, ; Vandevivere et al, ). Specifically, we found that SBS expectations can vary within individuals even across contexts with similar situational characteristics, and even when these expectations are assessed at the same point in time.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The current studies’ findings in favor of state attachment variability add to previous studies that found evidence for state attachment fluctuations (e.g., Bosmans, Van de Walle et al, ; Vandevivere et al, ). Specifically, we found that SBS expectations can vary within individuals even across contexts with similar situational characteristics, and even when these expectations are assessed at the same point in time.…”
Section: Discussionsupporting
confidence: 84%
“…More recently, however, scholars have started to approach attachment from a more dynamic, state‐like perspective, focusing on individual's “at‐the‐moment” attachment expectations and suggesting that attachment expectations are sensitive to context (Fraley, ; Kobak & Bosmans, ) . The first few studies into state attachment variability indicate that expectations of trust in caregiver support are immediately sensitive to experiences of support and conflict with the attachment figure (Bosmans, Van de Walle, Goossens, & Ceulemans, ; Vandevivere, Bosmans, Roels, Dujardin, & Braet, ). As these studies focused on state attachment variability across contexts with different situational characteristics, to date it remains largely unclear (a) whether state attachment fluctuations can also occur across contexts with similar situational characteristics, that is, across a variety of distressing situations, (b) whether state attachment variability has a unidimensional structure (i.e., expectations of overall trust vs. no‐trust in caregiver support) or comprises different components (e.g., expectations about support seeking, expectations about the effectiveness of support), (c) how degree of state attachment variability is associated with more general, trait‐like attachment expectations, and (d) how state attachment variability is associated with psychological well‐being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when designing the placebo trials (De Winter et al, 2017), neutral maternal behavior in the context of children's support seeking during distress actually appears insensitive or unresponsive. A recent study in middle childhood further supported this concern (Vandevivere, Bosmans, Roels, Dujardin, & Braet, 2017). After exposure to distress, children were attributed to one of two conditions: one condition in which their own mother provided secure base support and one condition in which mother was only physically available but provided no support.…”
Section: Discussionmentioning
confidence: 91%
“…As a result, adults in our study might have been more motivated to protect themselves from new harm. Instead, children are much more susceptible to positive attachment experiences [39] and may have been more motivated to retry to seek help in spite of earlier negative learning experiences.…”
Section: Discussionmentioning
confidence: 99%